Estimation of size at sexual maturity of blue crab, Portunus pelagicus in peninsular Malaysia - Norliyana Asemari,; Nur Atikah Matdah,; Simon Kumar Das,; Yosni Bakar, (Penerbit Universiti Kebangsaan Malaysia, 2018)
The size at the onset of maturity of the blue crab (Portunus pelagicus) is an important reference for decision making in fisheries management. The size at 50% sexual maturity (SOM50) was investigated for crabs from the opposite coasts (east and west) of peninsular Malaysia. A total of 1554 and 1546 crabs from Kuala Kedah (west) and Mersing (east), respectively were utilized. Four common models were used for estimating SOM50. The SOM50 estimated for females (113-118 mm) were higher than males (105-110 mm). Crabs from Kuala Kedah attained maturity at bigger size than crabs from Mersing. The Akaike information criterion corrected for small sample indicated that the models were comparable but Lysack’s model appeared the best for female crabs from Kuala Kedah. The use of gonadosomatic index (GSI) to estimate size at maturity for this species is not precise.